The Relationship Between Student Scientific Attitude and Mastery of Science Concepts in Grade IV Elementary School - Artaga, Rajendra Cakra (Jurnal Ilmiah Sekolah Dasar, 2021)
The research design used is to formulate problems and determine research objectives. The subjects in this study were all students who opened 58 respondents in the fourth grade of elementary school who were taken using the Cluster Random Sampling technique. The method used in this study discusses two variables, the independent variable is the scientific attitude of students and the determining variable is the mastery of science concepts for grade IV elementary school. The instrument of data collection in this study used measurement techniques about formative variables in the form of and a questionnaire sheet operated on 30 independent variables. Data were analyzed by parametric statistics or product-moment correlation. The results showed that the difference in the results of the scientific attitude data of students with mastery of science concepts, the data showed that count was 2,431 > ttable was 1,672 at the significance level = 0.05 with the number of respondents 58 students.